Measurement of copper serum level in Acute Myocardial Infarction patients and comparing with CKmb and Troponin - العلوني, نغم; محمد عماد خياط; باسم معروف (Latakia University Journal -Medical Sciences Series, 2024)
Background: Proving the presence of a significant increase in serum copper values in acute myocardial infarction patients and finding a relationship between high levels of copper and cardiac marker CKmb enables us to distinguish high risk acute myocardial infarction patients who need more stringent control of cardiac risk factors , intensive treatment , and close medical follow up . Identifying the group of high risk patients enables us to make the decision to perform invasive interventions faster . . Objectives: the main objective: Measuring the level of serum copper and CKmb in patients with acute myocardial infarction compared with normal people . Secondary objective: Study of the relationship between the level of copper in serum and the level of CKmb in patients with acute myocardial infarction . Materials and methods: Statistical study ( Case – Control ) , The research sample included 50 patients who were admitted to the emergency department at Tishreen University Hospital in Latakia within 12 hours of the appearance of clinical symptoms that indicate decreased myocardial ischemia during the time period between April 2022 – 2023 . The investigators included the research inclusion criteria . A sample of 25 patients attending the hospital for other reasons was taken during the same time period , with the aim of comparing the serum copper level with them and studying the correlation between the serum copper level and CKmb . The diagnosis of acute myocardial infarction was made by the doctors of the cardiology department at Tishreen University Hospital based on the clinical examination and symptoms , in addition to the results of the electrocardiogram and laboratory test values . Copper was also calibrated in the central laboratory at Tishreen University Hospital using the semi – automated HUMAN device using the colorimetric method , As for CKmb the calibration was done on automated devices in the hospital using the kinetic method . Results: Serum copper values are higher in patients with acute myocardial infarction compared to normal people. The value of serum copper in patients with acute myocardial infarction increases as the value of the cardiac marker CKmb increases Conclusion: Measuring the level of serum copper in patients with acute myocardial infarction to help assess the severity of the injury and thus help speed up appropriate treatment procedures and prevent the occurrence of serious complications. Further studies into the possibility of using copper chelators to reduce signs or slow the progression of ischemic heart disease .